Guerilla Marketing A Type Of Marketing Strategy For Company Development - Muminova Umidakhon Dilshod qizi; Muminova Umidakhon Dilshod qizi (Genius Publishing Group, 2023)
The article defines the concept of guerrilla marketing, as well as the experience of Uzbekistan in developing a guerrilla marketing strategy
Keywords: marketing; guerrilla marketing; strategy; competition